Revisiting hemodynamic definition: Incidence of chronic thromboembolic pulmonary hypertension following acute intermediate-high and high-risk pulmonary embolism - Bárbara Lacerda Teixeira; André Grazina; Ricardo Carvalheiro; Tiago Mendonça; Tiago Pereira da Silva; António Fiarresga; Ruben Ramos; Duarte Cacela; João Reis; Ana Galrinho; Luís Almeida Morais; Rui Cruz Ferreira (Thrombosis Update)
Background: The hemodynamic definition of pulmonary hypertension (PH) was updated, lowering the mean pulmonary arterial pressure (PAP) threshold to 20 mmHg and the pulmonary vascular resistance (PVR) to 2 Wood units. The impact of these revised criteria on the number of patients reclassified as PH has not been extensively studied, namely in chronic thromboembolic pulmonary hypertension (CTEPH) population. Since the true incidence of CTEPH after acute pulmonary embolism (PE) is debatable, we aimed to analyze the incidence of CTEPH after high-risk forms of acute PE according to the new 2022 ESC/ERS hemodynamic criteria. Methods: A prospective registry of consecutive intermediate-high- and high-risk PE patients submitted to catheter directed therapies (CDT) in a tertiary center was used. Clinical, echocardiographic, computed tomography angiography (CTA), right heart catheterization (RHC) and digital subtraction pulmonary angiogram (DSPA) data were collected at admission and at 3 months. Results: Among 25 patients, RHC revealed that 36 % of patients met the criteria for PH per the new guidelines, compared to 16 % under the previous definition (p = 0.010), resulting in 20 % being reclassified. Mean PAP and PVR differed significantly according to both definitions. Under the new definition, additional parameters of RHC also showed significant differences (p < 0.05). Perfusion defects were noted in 33 % of PH patients on DSPA but not on CTA, while the remained displayed them on both modalities. Among patients without PH, 31.3 % exhibited perfusion defects. Conclusion: According to the new updated criteria for PH, 36 % of intermediate-high- and high-risk PE patients met the criteria of CTEPH at 3 months of follow-up. With a possible rising incidence of CTEPH, special monitoring and management is crucial.